Impact of Simulator-Based Crisis Resource Management Training on Collective Orientation in Anaesthesia: Pre-Post Survey Study With Interprofessional Anaesthesia Teams - Markus Flentje; Hendrik Eismann; Lion Sieg; Vera Hagemann; Lars Friedrich (Journal of Medical Education and Curricular Development, 2020)
Theory: Individuals have different qualities, levels of willingness, and degrees of engagement for working in teams. This behaviour is termed ‘Collective Orientation’ (CO). Collective orientation can be trained and has a positive influence on team processes. Here, we investigated the effect of a simulator-based, Crisis Resource Management team training upon the participants’ CO. Hypotheses: We hypothesized (1) the scales of CO and Presence for lab-based microworld research (PLBMR) are applicable to the German anaesthesia teams, (2) the CO can be influenced by means of simulation training, (3) the training effect is dependent on sex and/or profession, and (4) the change of CO depends on the perceived presence of the participants in the scenario. Method: In a pre-post study, 66 nurses and doctors from various anaesthetic departments took part in a 1-day training course to improve non-technical skills. The primary outcome was the mean difference between the CO measured (via questionnaires) immediately before (T1) and after (T2) training. The change was then tested for dependence upon other variables, such as sex, professional group, and immersion into the simulation scenarios. Results: Collective orientation improved significantly after training (mean difference: 0.2; P  < .001; dz = 0.53). Considering the subscales, affiliation increased significantly ( P  < .001; dz = 0.59), whereas dominance remained unchanged. Furthermore, no correlation was found regarding sex, professional group, or immersion into the simulation scenarios. Conclusions: Our study demonstrated that simulation-based training improves the participants’ COs, primarily by increasing affiliation. Subjective scenario reality did not significantly influence this. Nonetheless, it remains unclear as to what factors categorically resulted in this benefit. The shared experience in the course by all team members might trigger the effects. However, further studies are needed to identify the modifiable factors that can improve teamwork attitudes.